Acute bacterial sinusitis in children: an updated review - Alexander KC Leung; Kam Lun Hon; Winnie CW Chu (BioExcel Publishing Ltd, 2020)
Background: In the pediatric age group, approximately 7.5% of upper respiratory tract infections (URIs) are complicated by acute bacterial sinusitis (ABS). Despite its prevalence, ABS is often overlooked in young children. The diagnosis and management present unique challenges in primary care. This is an updated narrative review on the evaluation, diagnosis, and management of ABS. Methods: A PubMed search was performed using the key term 'acute sinusitis'. The search strategy included clinical trials, meta-analyses, randomized controlled trials, observational studies, and reviews. The search was restricted to the English literature and children. Results: Haemophilus influenzae (non-typeable), Streptococcus pneumoniae, and Moraxella catarrhalis are the major pathogens in uncomplicated ABS in otherwise healthy children. In complicated ABS, polymicrobial infections are common. The diagnosis of acute sinusitis is mainly clinical and based on stringent criteria, including persistent symptoms and signs of a URI beyond 10 days, without appreciable improvement; a URI with high fever and purulent nasal discharge at onset lasting for at least 3 consecutive days; and biphasic or worsening symptoms. Conclusion: Data from high-quality studies on the management of ABS are limited. The present consensus is that amoxicillin-clavulanate, at a standard dose of 45 mg/kg/day orally, is the drug of choice for most cases of uncomplicated ABS in children in whom antibacterial resistance is not suspected. Alternatively, oral amoxicillin 90 mg/kg/day can be administered. For those with severe ABS or uncomplicated acute sinusitis who are at risk for severe disease or antibiotic resistance, oral high-dose amoxicillin-clavulanate (90 mg/kg/day) is the drug of choice.